Pengaruh Sistem Seleksi, Program Pelatihan, dan Kompetensi terhadap Kualitas Kerja serta Dampaknya terhadap Kinerja Perusahaan pada PT Darya Varia - Mentari, Azizah; Saifudin, Asep (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
This study aims to analyze the influence of the selection system, training programs, and competencies on work quality and their impact on company performance at PT. Darya Varia. The study population was all employees of PT Darya Varia. A sample of 100 employees was taken using a purposive sampling technique, with the criteria of minimum work experience of one year and direct involvement in the production and managerial processes, so that the data obtained was relevant to the focus of the study. The research instrument was a structured questionnaire with a Likert scale of 1–5, the collected data were analyzed using Structural Equation Modeling (SEM) through Partial Least Squares (PLS-SEM) software. The results showed that the selection system, training programs, and employee competencies had a positive and significant influence on work quality at PT Darya Varia, both partially and simultaneously. Competence was proven to be a dominant factor in determining work quality. Furthermore, work quality plays an important role in improving company performance and mediates the influence of the selection system, training, and competencies on company performance. Simultaneously, these three human resource variables are able to explain more than half of the variation in work quality and company performance. This shows the importance of integrating these three aspects in HR management to achieve organizational excellence